EDUKASI PROTOKOL KESEHATAN (3M) : MELALUI MEDIA GAME ATTACK OF THE KRONA - I Gede Adi Sudi Anggara; I Wayan Adi Putra Yasa; I Dewa Gede Agung Pandawana; I Nyoman Jayanegara (Prahasta Publisher (manage by: DRPM Institut Bisnis dan Teknologi Indonesia), 2022)
The pandemic due to the spread of the COVID-19 disease has led to changes in various social structures in society. The application of social distancing as a form of preventing the spread of disease raises the phenomenon of limiting various activities that present a large number of people. Various changes in the order of life then gave rise to a new life order (new normal) in responding to the COVID-19 epidemic. A creative effort is needed so that this new life order can be implemented in society from an early age. Games are creative solutions that combine elements of design and technology so that they are very easy to be accepted by various groups. In game design, assets are very important to design first. The design of this asset game will use a visual flat design style that has gone through a visual study process by collecting similar images or photos as a visual reference in the design. The resulting game assets display simplification of both illustrations and typography, the use of solid colors with game values, and a simpler user interface (UI).